Plasticity of Mesenchymal Stem Cells from Mouse Bone Marrow in the Presence of Conditioned Medium of the Facial Nerve and Fibroblast Growth Factor-2 - Eudes Euler de Souza Lucena; Fausto Pierdoná Guzen; José Rodolfo Lopes de Paiva Cavalcanti; Maria Jocileide de Medeiros Marinho; Wogelsanger Oliveira Pereira; Carlos Augusto Galvão Barboza; Miriam Stela Mariz de Oliveira Costa; Expedito Silva do Nascimento Júnior; Jeferson Sousa Cavalcante (The Scientific World Journal)
A number of evidences show the influence of the growth of injured nerve fibers in peripheral nervous system as well as potential implant stem cells (SCs). The SCs implementation in the clinical field is promising and the understanding of proliferation and differentiation is essential. This study aimed to evaluate the plasticity of mesenchymal SCs from bone marrow of mice in the presence of culture medium conditioned with facial nerve explants and fibroblast growth factor-2 (FGF-2). The growth and morphology were assessed for over 72 hours. Quantitative phenotypic analysis was taken from the immunocytochemistry for glial fibrillary acidic protein (GFAP), protein OX-42 (OX-42), protein associated with microtubule MAP-2 (MAP-2), protein β-tubulin III (β-tubulin III), neuronal nuclear protein (NeuN), and neurofilament 200 (NF-200). Cells cultured with conditioned medium alone or combined with FGF-2 showed morphological features apparently similar at certain times to neurons and glia and a significant proliferative activity in groups 2 and 4. Cells cultivated only with conditioned medium acquired a glial phenotype. Cells cultured with FGF-2 and conditioned medium expressed GFAP, OX-42, MAP-2, β-tubulin III, NeuN, and NF-200. This study improves our understanding of the plasticity of mesenchymal cells and allows the search for better techniques with SCs.